Suíte arqueana planalto e granitoides Vila Jussara, Província Carajás: um estudo morfológico e composicional de zircão através de MEV-CL-ERE-EDS - CUNHA, Renan Malone Brito (2019)
Zircon is a common accessory mineral in many igneous rocks, especially in felsic rocks. Zircon grains from different magmas tend to inherit geochemical signatures characteristic of their sources. The relatively high chemical stability to subsolidus changes, coupled with the presence of trace elements such as Hf, Y, Nb, Th, U, Ca, P and ETR in the crystal structure of zircon have allowed important advances in the characterization of source rocks, in identifying fractionation of igneous rocks, and in provenance studies. Therefore, morphological, textural and compositional variations in zircon crystals assist in the understanding of their history of crystallization and hence its host rock. In this context, this paper discusses the morphological and compositional aspects of zircons from Archean Planalto and Vila Jussara granites, located in the Canaã dos Carajás region, southeastern Amazonian craton, with the goal of establishing a morphological signature and geochemical feature of these bodies. Cathodoluminescence (CL) images, obtained using Scanning Electron Microscopy (SEM), allowed identifying internal features such as compositional zoning, inherited cores, edges of overgrowth, inclusions, fractures and features indicative of alterations. In general, the zircons from Planalto and Vila Jussara granites are morphologically similar. Their crystals are euhedral and luminescent, have well-defined compositional zoning, fractures towards core-edge, metamict cores and inclusions of F-apatite. However, zircons the sample RD-02 of Planalto Granite, from an area intensely deformed related to Itacaiúnas shear zone, presented dominantly anhedral to subhedral crystals with low intensity of luminescence (dark), free of obvious compositional zoning, and intensely fractured. These zircons are more compositionally enriched in Ca (0.4-1.2%), have the lowest Nb content (3.9-4.4%) and the lowest Nb/Ta (4.0 to 5, 8) and Zr/Hf (21-32) ratios, when compared to the zircon of RD-05 sample located outside the deformed region. This fact allows to infer that the percolation of fluids through fractures probably contributes to the ocurrence of the higher Ca contents observed in these zircons, as well the reduction of the Nb contents by means of replacement reactions. The zircons from Vila Jussara Granite have Ca content between 0.1 and 0.2%,Nb between 4.2 and 7.7% and Zr/Hf ratios ranging from 21 to 36.5. The application of SEM-EDS-ERE-CL in zircon confirms its importance as a complementary tool in petrological studies.